Prevalence And Characteristics Of E-cigarette Users Among Malaysian Current And Ex-smokers - Ho BK; Mohamad Haniki NM; Jamalludin AR; Samsul D; Mira K; Norny Syafinaz AR; Robson N; Chan CMH; Lim KH; Baharom N; Ismail N; Tee GH; et al. (Academy of Family Physicians of Malaysia, 2024)
Volume 14 Number 2